Phytohormones Regulate Both “Fish Scale” Galls and Cones on Picea koraiensis - Jia, Mingyue; Li, Qilong; Hua, Juan; Liu, Jiayi; Zhou, Wei; Qu, Bo; Luo, Shihong (Frontiers in Plant Science, 2020)
The larch adelgid Adelges laricis laricis Vallot is a specialist insect parasite of Picea koraiensis (Korean spruce), and forms fish scale-like galls that damage the growth of the host plants. Our investigation reveals that both these galls and the fruits (cones) of P. koraiensis display lower concentrations of phytosynthetic pigments and accumulate anthocyanin cyanidin-3-O-glucoside, and soluble sugars in the mature stages. Interestingly, high concentrations of 6-benzylaminopurine (BAP) both in the cauline gall tissues and in the larch adelgids themselves (4064.61 ± 167.83 and 3655.42 ± 210.29 ng/g FW respectively), suggested that this vital phytohormone may be synthesized by the insects to control the development of gall tissues. These results indicate that the galls and cones are sink organs and the development of gall tissues is possible regulated by phytohormones in a way similar to that of the growth of cones. The concentrations of phytohormones related to growth (indole-3-acetic acid [IAA], cytokinins [CTK], and gibberellins [GAs]) and defense (salicylic acid [SA]), as well as SA-related phenolics (benzoic acid [BA] and p-hydroxybenzoic acid [pHBA]) in gall tissues were positively correlated with those in cones during the development stage. The levels of 1-aminocyclopropane-1-carboxylic acid [ACC] in the developmental stage of the cones correlates negatively with their concentrations in the gall tissues (R= -0.92, P<0.001), suggesting that down-regulation of ACC might be the reason why galls are not abscised after a year. Our results provide a new perspective on the potential mechanism of the development of cauline galls on P. koraiensis, which are regulated by phytohormones.